Le regard des photographes commerciaux. Quelques clichés du fonds égyptien de la Collection Fouad Debbas à l’étude. - Yasmine Chemali; Anne-Hélène Perrot (Les Cahiers de l'École du Louvre)
The Collection Fouad Debbas in Beirut, which contains over 35,000 images (glass-plate negatives and positives, albumen and collodion prints, photographic albums, visiting cards, postcards, stereoscopic views, and old engravings and books) is probably one of the most important photographic collections on the Near East. A keen collector, Fouad Debbas was principally interested in the images produced in Beirut from the second half of the nineteenth century to the 1930s, about which he produced studies and publications. The collection also features many works dedicated to Egypt: from documentary to commercial photography, various photographic trends are represented. Based on a selection of works, the article takes a new look at the photographs and albums produced by professional photographers living in or visiting Egypt, for an essentially European clientele in the second half of the nineteenth century. Shortly after the invention of photography, Egypt, which was henceforth part of the Grand Tour, became a sought-after tourist destination. Professional photographers sought to produce a large number of images – souvenirs of cities and archaeological sites – for these new travelers while a certain taste for the indigenous portrait developed at the same time. The tricks uses by these photographers, between mise en scène and technical sophistication, are analysed here, witnesses to an orientalist and exotic discourse anchored in the nineteenth century.